Implementación de un sistema informático utilizando la metodología scrum, mediante dispositivos de posicionamiento global (gps) para el control de rutas de la compañía de transporte intracantonal de pasajeros Citibus s.a. de la ciudad de Latacunga, en el periodo septiembre 2015 – febrero 2016 - Bustillos Mallitásig, Ángela Karina (2016)
The Company of transport citibus s.a. which presents a problem on time control and faults of the units when they pass through different checkpoints, each backwardness produces sanctions that owner has to pay at less driver justifies the backwardness. The use of printed cards and manual registrations Makes the control can be seen altered by the double dial in the same place on the card which causes a non-legible form the exact date and time that was marked. This thesis project is the implementation of a Web application to control travel units called Control Route System (SCR) consists of an electronic device that has technology of Global Positioning System (GPS) and GPRS which is placed in each unit, those allow control the exact position that will be compared to the registration point with date and time instantly, which will help to reduce working risks.